Could Mineralocorticoids Play a Role in the Pathophysiology of Open Angle Glaucoma? - Christian Albrecht May (Journal of Ophthalmology)
Since the pathomechanisms of primary open angle glaucoma are still not defined, different aspects related to this topic have to be discussed and further investigated. Possible candidates are the mineralocorticoids, which are known to lower intraocular pressure. A data search and personal investigations assume a limited role of mineralocorticoids for the development of glaucoma. Specific experiments for a final conclusion are, however, not yet performed.